Calligraphy, Its historical roots and its philosophical and aesthetic impact - ATTIYA, Saad Jihad (Arab Journal for Sciences and Research Publishing, 2022)
This study revolves around the subject of Arabic calligraphy with its deep cultural roots, the stages of its development, progress, advancement and interaction in the field of art and its aesthetic philosophy, and its embodiment as a form of fine art by incorporating it into the artistic painting as an element or an artistic dimension, thus generating harmony, or the fusion of symbols and their interaction. And writing does not necessarily mean Arabic calligraphy because the difference between them is great and cannot be confused, as the word calligraphy is a term associated with the Arabic calligraphy that was invented and developed by Muslims and contains different styles and types of craft drawings governed by rules set by calligraphers, and they developed with the passage of time until it settled on its current known form In order to know the Arabic calligraphy, we will find that the word calligraphy means (line with the pen), i.e. books or drawing, and also calligraphy has been associated with writing in other civilizations, they are non- Arab, so this definition has a kind of comprehensiveness What draws attention in this study is the richness of the Arabic letter and its formation as an artistic element through its interaction with the art of decoration and engineering design, and this is since the early ages of awareness when the Sumerians were symbolically drawing cuneiform letters in the syllabic writing stage. Its beginnings were with illustrations, it developed until it returned to written letters, then moved to formation, and it became (art is inspired by the letter). From the beginning, we must get to know this human discovery that prompted man to write down and write through the discovery of this symbol or sign and letter. It seems that the development of Arabic calligraphy and the creativity that accompanied all its stages until it reached the beautiful art it reached, and acquired the splendor of the geometric form formed by a group of letters by forming a painting; we may not find this in other forms of fonts. The Arabic calligraphy in which the Noble Qur’an was written transmitted all the symbols of aesthetics and majesty, and moved to the neighboring and distant world through the Islamic conquests. Wherever it came, it was an acceptable symbol and a civilized dimension. The beauty of this calligraphy would not have been achieved without this effort made by those figures through their desire to elevate this beautiful art. Its aesthetic depth lies in its possessing the spirit of renewal and development.